Anti-melanoma vaccinal capacity of CD11c-positive and CD11c-negative cell populations present in GM-CSF cultures derived from murine bone marrow precursors - Campisano, Sabrina Edith (2013)
We have initially shown that DC/ApoNec vaccine can induce protection against the poorly immunogenic B16F1 melanoma in mice. The population of DC obtained for vaccination after 7days culture with murine GM-CSF is heterogeneous and presents about 60% of CD11c+ DC. Therefore, our purpose was to identify the phenotype of the cells obtained after differentiation and its immunogenicity once injected. DC were separated with anti-CD11c microbeads and the two populations identified in terms of CD11c positivity (DC+ and DC-) were also studied. Approximately 26.6% of the cells in DC+ fraction co-expressed CD11c+ and F4/80 markers and 75.4% were double positive for CD11c and CD11b markers. DC+ fraction also expressed Ly6G. DC- fraction was richer in CD11c-/F4/80+ macrophages (44.7%), some of which co-expressed Ly6G (41.8%), and F4/80-/Ly6-G+ neutrophils (34.6%). Both DC+ and DC- fractions displayed similar capacity to phagocyte and endocyte antigens and even expressed levels of MHC Class II and CD80, CD83 and CD86 costimulatory molecules similar to those in the DC fraction. However, only DC/ApoNec vaccine was capable to induce protection in mice (p<0.01). After 24h co-culture, no detectable level of IL-12 was recorded in DC/ApoNec vaccine, either in supernatant or intracellularly. Therefore, the protection obtained with DC/ApoNec vaccine seemed to be independent of the vaccine´s ability to secrete this inflammatory cytokine at the time of injection. In conclusion, we demonstrated that all cell types derived from the culture of mouse bone marrow with GM-CSF are necessary to induce antitumor protection in vivo.